Thriving in Olympic cycling: An athlete-centered approach to understanding the promotion of athlete well-being and performance in Olympic environments - Brown, D. J. (North American Society for the Psychology of Sport and Physical Activity Virtual Conference - 11 Jun 2020 - 12 Jun 2020, 2020)
With growing concerns about the win-at-all-costs mentality present in high-performance sporting environments, a shift in attention is required to protect and promote athlete welfare. The aim for this project was to offer novel insight into how elite sport environments can be shaped to promote both high performance and well-being (i.e., thriving). A longitudinal design was employed with one-to-one interviews conducted with eleven international track cyclists on three occasions over a six-month period. Interview data were iteratively analyzed using reflexive thematic analysis to construct themes and describe areas of change. From this analysis, themes were presented as demands (e.g., lack of income, need for results and improved performance) and supports (e.g., mind-coach, non-sport friends), with some social agents (e.g., coach, family, training partners) and environmental features (e.g., concurrent study or vocational commitments) labeled as both demands and supports. Themes were also constructed for environmental areas of improvement pertaining to the coaching team, the Federation, innovation and expertise, and squad cohesion. Lastly, agents of changes (e.g., race schedule, selection decisions) were forwarded as events and circumstances which created fluctuations in the cyclists` experiences. The findings from this study provide the first longitudinal account of sport performers` attempts to thrive in high-performance environments and, thus, represent a unique attempt to understand these experiences over time. These findings are discussed in line with practical applications, offering coaches and practitioners a better understanding of how to facilitate thriving in their Olympic athletes.